Pharmacokinetics of peramivir after single intravenous doses in healthy Chinese subjects. (March 2015) - Zhang, Dan; Du, Aihua; Zhang, Lina; Ma, Jingyi; Meng, Lingjie; Deng, Ming; Xu, Juan; Liu, Huichen
Abstract 1. The aim of the study was to evaluate the pharmacokinetics of peramivir after single intravenous (i.v.) doses in healthy Chinese subjects. 2. In a cross-over study, 12 subjects were given 300 and 600 mg peramivir by i.v. infusion. Blood and urine samples were collected at 17 designated time points and 7 designated intervals up to 36 h post-dose. Plasma and urine concentrations of peramivir were quantified by LC-MS/MS. 3. After single i.v. doses of 300 and 600 mg peramivir, Cmax and AUC0–t of peramivir were 21.4 ± 3.7, 41.1 ± 5.3 mgċL−1 and 55.90 ± 10.62, 112.1 ± 13.2 mgċh L−1, respectively. Cmax and AUC increased in proportion to the dose. Within 12 h, accumulative urinary recoveries of peramivir after single i.v. doses of 300 and 600 mg peramivir were 84.31 ± 11.75% and 88.10 ± 7.39%, respectively. 4. In healthy Chinese subjects, peramivir displayed linear pharmacokinetics in the range of 300–600 mg, and was primarily excreted via urine as unchanged drug.